Longitudinal development of depression and anxiety during COVID-19 pandemic in Germany: Findings from a population-based probability sample survey - Giel, Katrin E.; Martus, Peter; Paul, Gregor; Jürgensen, Jan Steffen; Löwe, Bernd; Serna Higuita, Lina Maria; Dörsam, Annica F.; Stuber, Felicitas; Ehehalt, Stefan; Zipfel, Stephan; Junne, Florian (Frontiers in Psychiatry, 2022)
The stress response to the COVID-19 pandemic might differ between early and later stages. Longitudinal data on the development of population mental health during COVID-19 is scarce. We have investigated mental health trajectories and predictors for change in a probability sample of the general population in Germany at the beginning and after six months of the pandemic. We conducted a longitudinal survey in a population-based probability sample of German adults. The current study analysed data from a first assessment in May 2020 (T1; N = 1412) and a second in November 2020 (T2; N = 743). Mental health was assessed in terms of anxiety and depression using the Patient Health Questionnaire-4 (PHQ-4). Mental health outcomes at T1 were compared with PHQ-4 norm data. Trajectories over time were investigated based on outcome classifications of PHQ-4 scores. Predictors of mental health outcomes and change were identified using multiple regression analysis. In spring 2020, participants showed significantly higher PHQ-4 scores as compared to the norm data, however, overall anxiety and depression remained low also six months later. 6.6% of respondents showed a mental health deterioration in autumn 2020, entering subclinical and clinical ranges, outweighing the proportion of people with improved outcomes. Sociodemographic variables associated with mental distress at T1 were mainly not predictive for change at T2. Even under prolonged pandemic-related stress, mental health remained mainly stable in the general population. Further development of the considerable subgroup experiencing deterioration of depression and anxiety should be monitored, in order to tailor prevention and intervention efforts.